Amphibious superamphiphilic fabrics with self-healing underwater superoleophilicity. Issue 1 (4th October 2018) - Fu, Sida; Zhou, Hua; Wang, Hongxia; Niu, Haitao; Yang, Weidong; Shao, Hao; Lin, Tong
Abstract : A fabric with novel amphibious superamphiphilicity and self-healing underwater superoleophilicity has been developed using a single-step wet-chemical coating technique. Abstract : Most of the superamphiphilic surfaces reported so far show an oleophobic feature in underwater environments because once they are wetted with water their wettability is governed by the water layer adsorbed on the surface. In contrast, underwater oleophilic surfaces often show superhydrophobicity–oleophilicity in a dry state in air. A challenge remains in developing a superamphiphilic surface that shows both superhydrophilicity and underwater superoleophilicity ( i.e. underwater superamphiphilicity). Herein, we demonstrate a novel strategy to prepare a surface that simultaneously possesses superamphiphilicity in air and underwater environments (also referred to as "amphibious superamphiphilicity" in this paper). A single-step wet-chemical coating method was employed to apply a crosslinkable polymer material, which consists of hydrophilic and oleophilic functional groups, onto a fabric substrate. The fabric after coating treatment exhibited amphibious superamphiphilicity with a contact angle of 0° for water and oils. In the dry state, it took less than 1 second for water and oil fluids of surface tension in the range of 18.4–50.8 mN m −1 to spread completely on the surface. In water, although the fabric was quickly wetted, it still allowed oils to spread completely into the wetted fabric matrix in less than 1 minute. More interestingly, the underwater superoleophilicity is self-healable against chemical damage. We further showed that such amphibious superamphiphilicity has great potential for recovery of oil from water. No matter whether the fabric was in a dry or pre-wetted state, it showed a similar oil absorption capability. The high resilience against moisture environments made oil recovery very stable. In addition, the coating is durable enough against various types of harsh damage. Such unusual superamphiphilicity may offer novel properties and applications in diverse fields.